GAMBARAN PERAWATAN HIPERTERMI PADA ANAK SAKIT DI RUMAH SAKIT - Ribek Nyoman ribek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
Overview of Hypertermia Care in Sick Children at the Hospital. The purpose of this study was to obtain an overview of the hyperterm care carried out in sick children at the hospital. This study uses a qualitative research design with a case study approach. The participants of this study were 6 people, namely 2 nurses who treated sick children and 4 sick children who were being treated. Participants were considered valid as informants because the 2 nurses had experience in hyperthermia care in the orchid room while 4 sick children were considered valid as information during observation of participation. Data from interviews, observations and documentation were analyzed according to miles and huberman including reduction, presentation and verification. It was concluded that hyperthermia in typhoid patients and dengue fever had a body temperature above 3.7 degrees of Celcius and was given paracetamol as a fever with education to drink lots and warm compresses could come down within 3 days.